FIGHTER MOLECULES AGAINIST TO CANCER - PEPTIDE VACCINES - Ergin, Buket; Pelit Arayici, Pelin; Mustafaeva, Zeynep; Mamedov, Baxtiyar (YILDIZ TECHNICAL UNIV, 2017)
Cancer is one of the biggest disease of our age. Chance of survival decreases as the diagnosis prolongs. Being an insidious disease makes it harder to determine and diagnose early for cancer. There are lots of studies about fighting this disease. In recent years, vaccine studies have gotten important to prevent cancer. Although cancer vaccine studies have a long history, studies which use peptide vaccines for cancer are applied about last 20 years. Peptide vaccines are created by using peptide sequences which generate the disease as template. The aim is to destroy the tumour antigens by T lymphocytes which are activated by the immune system using peptide sequences.
Keywords: Cancer; peptide vaccine; carrier molecules; immunotherapy; SYNTHETIC PEPTIDE; IDENTIFICATION; DESIGN; BREAST; DRUG; Engineering